Extraordinary sensitivity for H2S and Fe(iii) sensing in aqueous medium by Al-MIL-53-N3 metal–organic framework: in vitro and in vivo applications of H2S sensing. Issue 8 (7th February 2018) - Das, Aniruddha; Banesh, Sooram; Trivedi, Vishal; Biswas, Shyam
Abstract : An Al-MIL-53-N3 MOF sensor showing extraordinary sensitivity for H2 S and Fe(iii ) is presented. Its cell imaging capability is also demonstrated. Abstract : An Al(iii ) metal–organic framework (MOF) called Al-MIL-53-N3 (1 ) was synthesized under solvothermal reaction conditions using Al(NO3 )3 ·9H2 O and H2 BDC-N3 (H2 BDC-N3 = 2-azido-1, 4-benzenedicarboxylic acid) ligand in a DMF/water (DMF = N, N -dimethylformamide) mixture. Phase purity was checked by performing X-ray powder diffraction, infrared spectroscopy and thermogravimetric analysis. Thermogravimetric analysis suggests that1 is highly stable up to 300 °C under air atmosphere. The activated1 (called1′ ) showed a very fast fluorescence response to H2 S (turn-on) and Fe(iii ) ions (turn-off) in an aqueous medium with excellent sensitivity and selectivity even in the presence of other potentially intrusive analytes. In the presence of H2 S, the conversion of the azide moiety to amine is responsible for the fluorescence turn-on properties. On the other hand, the partial replacement of framework Al(iii ) ions by Fe(iii ) can be assigned for the selective detection behavior to Fe(iii ) ions. The detection limits (90.47 nM for H2 S and 0.03 μM for Fe(iii ) ions in water) of1′ are lower than those of the formerly reported MOF type of fluorescent sensors. The1′ -loaded J774A.1 macrophage cells are healthy and respond to intracellular H2 S to exhibit strong blue fluorescence, confirming its suitability to detect H2 S inside the cells. In addition, 1′ can detect H2 S in human blood plasma (HBP) and sulfide ions in real water samples. These features make1′ a very promising candidate for the on-site sensing of Fe(iii ) ions and the detection of intracellular and extracellular H2 S.